2007
DOI: 10.1002/jcb.21466
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lipopolysaccharide‐induced inducible nitric oxide synthase and cyclooxygenase‐2 gene expression by 5‐aminoimidazole‐4‐carboxamide riboside is independent of AMP‐activated protein kinase

Abstract: Recent studies suggest AMP-activated protein kinase (AMPK), an enzyme involved in energy homeostasis, might be a novel signaling pathway in regulating inflammatory response, but the precise intracellular mechanisms are not fully understood. In this study, we have demonstrated that 5-aminoimidazole-4-carboxamide riboside (AICAR), an activator of AMPK, inhibited lipopolysaccharide (LPS)-induced protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in macrophages and microglial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 34 publications
8
59
1
Order By: Relevance
“…There are published examples of AMPK-independent roles for both of these compounds (63,64), stressing the importance of using genetic models to corroborate pharmacologic data. Even after taking this caveat into account, the genetic evidence for the role of AMPK is also not always clear-cut, sometimes even when the same pathways are being scrutinized.…”
Section: Discussionmentioning
confidence: 99%
“…There are published examples of AMPK-independent roles for both of these compounds (63,64), stressing the importance of using genetic models to corroborate pharmacologic data. Even after taking this caveat into account, the genetic evidence for the role of AMPK is also not always clear-cut, sometimes even when the same pathways are being scrutinized.…”
Section: Discussionmentioning
confidence: 99%
“…Isoda et al (2006) reported that metformin reduces high-glucose induced proinflammatory signaling independent of AMPK activation in human saphenous vein endothelial cells. Another AMPK activator, 5-aminoimidazole-4-carboxamide riboside, was shown to exhibit anti-inflammatory effects independent of the activation of AMPK in RAW264.7 cells stimulated with LPS (Jhun et al, 2004;Kuo et al, 2008). These observations indicate that the inhibitory effects of metformin on the production of TNF and TF in LPS-or oxLDL-stimulated monocytes might be independent of its activation of AMPK.…”
Section: Inhibition Of Egr-1 Expression By Metformin 209mentioning
confidence: 92%
“…Although many effects of AICAR are at least partially dependent on AMPK, in many cases the effects of AICAR are AMPKindependent (11)(12)(13)(14)(15), suggesting the existence of additional AICAR targets. Interestingly, in yeast the AMPK homolog named Snf1 appears unaffected by AICAR (16).…”
Section: Amino-imidazole Carboxamide Ribonucleotide Monophosphate (Aimentioning
confidence: 99%